2007
DOI: 10.1089/end.2007.9914
|View full text |Cite
|
Sign up to set email alerts
|

Water under the Bridge: 5-Year Outcomes after Percutaneous Ablation of Obstructing Parapelvic Renal Cysts

Abstract: Percutaneous endocystolysis is an effective minimally invasive treatment option for obstructing parapelvic cysts and is associated with excellent 5-year outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 14 publications
1
20
1
Order By: Relevance
“…Aspiration alone is associated with a high recurrence rate, as demonstrated in one of our patients. Laparoscopic management remains the favoured option, particularly in patients with multiple or anteriorly located parapelvic cysts [2]. However, laparoscopic decortication for parapelvic cysts is technically more challenging and associated with significantly greater blood loss and operative time compared to surgery for peripherally sited simple cysts, though both procedures have similar complication rates [3].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Aspiration alone is associated with a high recurrence rate, as demonstrated in one of our patients. Laparoscopic management remains the favoured option, particularly in patients with multiple or anteriorly located parapelvic cysts [2]. However, laparoscopic decortication for parapelvic cysts is technically more challenging and associated with significantly greater blood loss and operative time compared to surgery for peripherally sited simple cysts, though both procedures have similar complication rates [3].…”
Section: Discussionmentioning
confidence: 99%
“…However, laparoscopic decortication for parapelvic cysts is technically more challenging and associated with significantly greater blood loss and operative time compared to surgery for peripherally sited simple cysts, though both procedures have similar complication rates [3]. Antegrade percutaneous nephroscopic ablation, with cyst wall fulguratation using a resectoscope with a rollerball electrode, has also been demonstrated to be safe and effective [2]. More recently, retrograde management with flexible ureteroscopy and incision and drainage of the renal cyst wall using a holmium laser has been demonstrated to be safe and effective [5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,14,15 Ureteroscopic marsupialization was first reported in 1991 5 as a complete transurethral natural orifice translumenal endoscopic surgery (NOTES) 16 that was significantly less invasive than percutaneous nephroscopy or laparoscopy. 4,14 Unfortunately, no large case series studies have reported on the success of this technique in the management of simple renal cysts. To investigate the feasibility and safety of this technique, we retrospectively examined the results of retrograde ureteroscopic marsupialization in the management of symptomatic simple renal cysts using 2 years of follow-up data.…”
Section: Introductionmentioning
confidence: 99%